Determinan Sosial Ekonomi Terhadap Kejahatan Kerah Putih - Yusuf Adiandaru; Sitti Retno Faridatussalam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the influence of socio-economic factors on white-collar crime in Indonesia, data taken from 34 provinces during 2017–2023. Using quantitative data taken from the Central Bureau of Statistics of Indonesia. This study uses quantitative analysis through panel data regression, where the Fixed Effect Model (FEM) was selected as the best method after testing with the Chow and Hausman tests. The study findings indicate three main results: first, there is a significant negative relationship between the unemployment rate and white-collar crime; second, a significant positive relationship was found between GRDP per capita and the white-collar crime rate; third, the average length of schooling and the Gini ratio were found to be insignificant with white-collar crime. The findings illustrate that increased economic activity can increase the chances of white-collar crime, while high unemployment actually reduces access to strategic positions that allow for such crimes. The implications of these results emphasize the importance of good supervision and governance in preventing misuse of economic resources along with economic growth.